Quantitative economic research: trends and problems - Kuznets, Simon; Kuznets, Simon Smith (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1972)
This book is outcome of papers presented at National Bureau of Economic Research fiftieth anniversary Colloquium.
Includes bibliographical references.
ijb 17/01/2019
Loans
Keywords: Economics; Econometrics